Estrogen-related receptor γ controls sterol regulatory element-binding protein-1c expression and alcoholic fatty liver - Kim, Don-Kyu; Feng, Rilu; Dooley, Steven (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2019)
Although SREBP-1c regulates key enzymes required for hepatic de novo lipogenesis, the mechanisms underlying transcriptional regulation of SREBP-1c in pathogenesis of alcoholic fatty liver is still incompletely understood. In this study, we investigated the role of ERRγ in alcohol-mediated hepatic lipogenesis and examined the possibility to ameliorate alcoholic fatty liver through its inverse agonist. Hepatic ERRγ and SREBP-1c expression was increased by alcohol-mediated activation of CB1 receptor signaling. Deletion and mutation analyses of the Srebp-1c gene promoter showed that ERRγ directly regulates Srebp-1c gene transcription via binding to an ERR-response element. Overexpression of ERRγ significantly induced SREBP-1c expression and fat accumulation in liver of mice, which were blocked in Srebp-1c-knockout hepatocytes. Conversely, liver-specific ablation of ERRγ gene expression attenuated alcohol-mediated induction of SREBP-1c expression. Finally, an ERRγ inverse agonist, GSK5182, significantly ameliorates fatty liver disease in chronically alcohol-fed mice through inhibition of SREBP-1c-mediated fat accumulation. ERRγ mediates alcohol-induced hepatic lipogenesis by upregulating SREBP-1c expression, which can be blunted by the inverse agonist for ERRγ, which may be an attractive therapeutic strategy for the treatment of alcoholic fatty liver disease in human.